Differential Exchange of Multifunctional Liposomes Between Glioblastoma Cells and Healthy Astrocytes via Tunneling Nanotubes - Formicola, Beatrice; D'Aloia, Alessia; Dal Magro, Roberta; Stucchi, Simone; Rigolio, Roberta; Ceriani, Michela; Re, Francesca (Frontiers in Bioengineering and Biotechnology, 2019)
Despite advances in cancer therapies, nanomedicine approaches included, the treatment of glioblastoma (GBM), the most common, aggressive brain tumour, remains inefficient. These failures are likely attributable to the complex, and not yet completely know, biology of this tumour, which is responsible for its strong invasiveness, high degree of metastasis, high proliferation potential and resistance to radiation and chemotherapy. The intimate connection through which the cells communicate between them plays an important role in these biological processes. In this scenario, tunneling nanotubes (TnTs) are recently gaining importance as a key features in tumor progression and in particular in the re-growth of GBM after surgery. In this context, we firstly identified structural differences of TnTs formed by U87-MG cells, as model of GBM cells, in comparison to those formed by normal human astrocytes (NHA), used as a model of healthy cells. Successively, we have studied the possibility to exploit U87-MG TnTs as drug-delivery channels in cancer therapy, using liposomes composed of cholesterol/sphingomyelin and surface functionalized with mApoE and chlorotoxin peptides (Mf-LIP) as nanovehicle model. The results showed that U87-MG cells formed almost exclusively thick and long protrusions, while NHA formed more thin and short TnTs. Considering that thick TnTs are more efficient in transport of vesicles and organelles, we showed that fluorescent-labelled Mf-LIP can be transported via TnTs between U87-MG cells, and with less extent through the protrusions formed by NHA cells. Our results demonstrate that nanotubes are potentially useful as drug-delivery channels for cancer therapy, facilitating the intercellular redistribution of this drug in close and far away cells, thus reaching isolated tumour niches that are hardly targeted by simple drug diffusion in the brain parenchyma. Moreover, the differences identified in TnTs formed by GBM and NHA cells can be exploited to increase treatments precision and specificity.